Genomic and proteomic adaptations to growth at high temperature - Hickey, Donal A (BioMed Central, 2004)
Most positively selected mutations cause changes in metabolism, resulting in a better-adapted phenotype. But as well as acting on the information content of genes, natural selection may also act directly on nucleic acid and protein molecules. We review the evidence for direct temperature-dependent natural selection acting on genomes, transcriptomes and proteomes.